2023
DOI: 10.3389/fpubh.2023.1220160
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ and patients’ assessments of listed mobile health apps in China: a qualitative study

PeiYu Liu,
XueYun Li,
Xiao Man Zhang

Abstract: BackgroundIn recent years, mobile health (mHealth) has gradually developed in China, and intelligent medicine has become an important research topic. However, there are still significant problems in mHealth applications (apps). Although healthcare professionals and patients are the main users, few studies have focused on their perceptions of the quality of mHealth apps.ObjectiveThis study aimed to (1) understand the respective perceptions of healthcare professionals and patients regarding mHealth apps, (2) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The relationship between digital health technology and patient security has gradually attracted everyone's attention. Liu et al's study found that virtual medical treatment brought insecurity to users [43]. This study found that the insecurity mainly came from the concern of older patients with COPD that remote technology could not replace some faceto-face medical services, resulting in lower medical quality.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between digital health technology and patient security has gradually attracted everyone's attention. Liu et al's study found that virtual medical treatment brought insecurity to users [43]. This study found that the insecurity mainly came from the concern of older patients with COPD that remote technology could not replace some faceto-face medical services, resulting in lower medical quality.…”
Section: Discussionmentioning
confidence: 96%